Instrumente moderne de cercetare a fenomenologiei administrative prin intermediul dinamicii sistemelor în contextul analizei sistemice a politicilor publice - Cristina Elena NICOLESCU (Revista Transilvană de Ştiinţe Administrative, 2011)
Recorded among the research methods in administrative sciences, operational (prospective) research increasingly attracts the interest of researchers in the field, due to the progresses and results it registers in the process of analysis of the complex transformations occurring in the social system. The movement of focus from the legitimacy of governments to that of public administrations determined a thorough research of the types and mechanisms of public intervention, in general, and of public policies, in particular, meant to explain and enrich the process of the public policy by identifying and promoting a new methodology of elaborating the optimum public policy variants, having as result the maximization of the benefits obtained by implementing them. For this purpose, and starting from the premise of the dynamic evolution of public policy seen as a system, the paper suggests a consolidated methodology which introduces, with the aid of the conceptual magnifying glass of systemic thinking and of systems dynamics – variant of the General Systems Theory, simulation and evaluation within complex models, future scenarios corresponding to the implementation of different variants of public policy.